The Feasibility of Usage TiN and CrN Barrier Sublayers for Improving the Adhesion of Polycrystalline Diamond Films on WC-Co Hard Alloys - Linnik S. A. Stepan Andreevich (Advanced Materials and Alloys, Nanomaterials and Nanotechnology, 2016)
Title screen